1998
DOI: 10.1159/000025890
|View full text |Cite
|
Sign up to set email alerts
|

Role of Kinins in the Renoprotective Effect of Angiotensin–Converting Enzyme Inhibitors in Experimental Chronic Renal Failure

Abstract: The aim of this study was to investigate whether the renoprotective effect of angiotensin–converting enzyme inhibitors (ACEIs) following 5/6 renal mass reduction is due in part to the potentiation of kinins. Three groups of rats with 5/6 renal mass reduction were studied during the 14 weeks following surgery. One group received no therapy (control); the second group was treated from the beginning with the ACEI ramipril (1 mg/kg/day) added to the drinking water, and the last group received ramipril plus a β Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 23 publications
0
12
1
Order By: Relevance
“…Therefore, we used SPH to investigate its renoprotective effects in an L-NAME-induced hypertensive model, and we found a reduction in renal ACE activity and proteinuria in rats fed SPH, but no significant reduction in creatinine was found. Although Relative density captopril was shown to bring high creatinine levels back to normal (22), another ACE inhibitor, ramipril, decreased the blood pressure and prevented proteinuria without affecting plasma creatinine in rats with chronic renal failure (23). These inconsistent results suggest that different substances with ACE-inhibitory activities may exhibit different effects, and SPH in the present study may have been sufficient to partially correct renal alterations caused by an NO deficiency, but not to completely overcome all of them.…”
Section: Discussioncontrasting
confidence: 56%
“…Therefore, we used SPH to investigate its renoprotective effects in an L-NAME-induced hypertensive model, and we found a reduction in renal ACE activity and proteinuria in rats fed SPH, but no significant reduction in creatinine was found. Although Relative density captopril was shown to bring high creatinine levels back to normal (22), another ACE inhibitor, ramipril, decreased the blood pressure and prevented proteinuria without affecting plasma creatinine in rats with chronic renal failure (23). These inconsistent results suggest that different substances with ACE-inhibitory activities may exhibit different effects, and SPH in the present study may have been sufficient to partially correct renal alterations caused by an NO deficiency, but not to completely overcome all of them.…”
Section: Discussioncontrasting
confidence: 56%
“…A similar observation was reported by Shimamoto et al [20] who showed a reduction in the excretion of urinary kallikrein that correlated with an increase in blood pressure indicating that tubulointerstitial inflammation may be responsible for a deficient activity of the KKS and the development of hypertension. Further, kinins have been implicated in partially mediating the beneficial effects of angiotensin-converting enzyme inhibitors in rats with chronic renal failure [21] though experiments using the kinin B2 antagonist HOE140 have failed to prove it [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…It is commonly accepted that with ACE inhibitors, the bradykinin lev-els increase, and the angiotensin II levels decrease, whereas with ARBs the bradykinin levels remain unchanged, and the angiotensin II levels actually increase. The role of bradykinin, however, remains controversial [24,25]. Conceivably, ARBs may be protective in hypertensive models, whereas ACE inhibitors may be preferred when the blood pressure is but mildly elevated.…”
Section: Discussionmentioning
confidence: 99%